The effect of black rice (Oryza sativa L. Indica) extract to increase estrogen hormone on pre-menopause of female white rats (Rattus norvegicus) - Ardiansyah Ardianyah; Mahrun Mahrun (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The study aimed to determine the estrogenic activity of extracting ethanol from black rice (Oryza Sativa L. Indica) in pre-menopausal female white rats (Rattus norvegicus). Adaptation was carried out on 20 female rats (Rattus norvegicus) experimental rats for one week with a body weight of about 200-250 g. After one week, the experimental rats were divided into five treatment groups, with each group consisting of 4 rats. The positive control group (P1) was given Ethinyl estradiol orally at a dose of 9Ãâ10-3 mg/ 200g BB in CMC-Na 1% as much as 3 mL. The negative control group (P2) was given orally CMC-Na 1% / 200g BW as 3 mL. Test Group I (P3) were given orally an extract of Black Glutinous Rice mixed with ethanolic basil leaves 96% with a dose equivalent to 1 mL of thick extract in an amount of 0.8g/200g BW in 1% CMC-Na as much as 3 mL. Test Group II (P4) was given an extract of the ethanol substance in Black Rice with a dose equivalent to 2 mL of thick extract in 1.6g/200g BW in 3 mL of 1% CMC-Na orally. Test Group III (P5) was given orally Black Glutinous Rice in a dose equivalent to 4 mL of thick extract in 3.2g/200g BB in CMC-Na 1% as much as 3 mL. The treatments were carried out orally for one estrous cycle begins during the estrus phase. Uniformity during the estrus phase was carried out using the Whitten-Method Effect. It aims to observe changes in the vagina to determine the estrus cycle by placing the male rat cage on top of the female rat cage. Conclusions from the results of this study show that the Black Glutinous Rice (Oryza Sativa L. Indica) extract treatment can increase the estrogenic activity of white rats pre-menopausal females (Rattus norvegicus). A 0.8g/200g BW dose can prolong the estrus cycle and increase vascularity and ovarian weight compared to the negative control (CMC-Na1%). The treatment with the lowest concentration was equivalent to the positive control of Ethinyl estradiol (9x10-3mg/200g BW). This test indicates that giving 96% ethanol extract of Black Glutinous Rice causes an increase in the hormone estrogen in the estrus phase, which tends to prolong the estrus cycle.